Return temperature after heat shock affects the production of tetraploids in the yellowtail tetra Astyanax altiparanae - Martins, Leandro Freitas; Hilbig, Cleonice Cristina; Yasui, George Shigueki; Monzani, Paulo Sergio; Senhorini, Jose Augusto [UNESP]; Okada Nakaghi, Laura Satiko [UNESP]; Nascimento, Nivaldo Ferreira do [UNESP] (Cambridge Univ Press, 2021)
The aim of this study was to evaluate different post-shock temperatures for tetraploid induction in the yellowtail tetra Astyanax altiparanae. Newly fertilized eggs were divided into four groups, three were submitted to heat shock (40 degrees C for 2 min) at 24 min post-fertilization (mpf) and another group remained without shock (control). Groups submitted to temperature shock were further separated at the following temperatures: 22 degrees C, 26 degrees C and 28 degrees C. Survival among embryonic development was counted and at hatching the ploidy was analyzed by flow cytometry. The results showed that the post-shock temperature affects the parameters analyzed and, therefore, must be considered for optimization of the production of tetraploid in A. altiparanae. Those data are innovative and could be used in future studies of basic biology in this species.
Keywords: Aquaculture; Chromosome manipulation; Flow cytometry; Polyploid; Triploid